Excessive interest of the husband in his wife and its impact on reducing the status of the man in the family Case study: Family Guidance and Protection Association in Tartous Governorate (Damascus University Journal of arts and humanities sciences, 2026)
The current research aims to identify the changes that occurred in the family after the man showed excessive interest in his wife, the most important changes that occurred in the wife's behavior, and the reasons that led to the decline in the man's status in the family. The research relied on the descriptive analytical approach, the social survey method by sample, using the questionnaire tool prepared by the researchers.A purposeful sample of men and women who frequent the Family Guidance and Protection Association in the city of Tartous was selected, and questionnaires were distributed to them to collect information. After obtaining the data, it was emptied using the (SPSS) program, and the appropriate statistical operations were conducted for the research. The research reached several results, the most important of which are: that excessive interest fromthe husband leads to a gradual decline in his status within the family, as the wife becomes more in control of family decisions, which may lead to the man feeling marginalized and losing his traditional role as head of the family.Also, the change in the distribution of roles between spouses can lead to problems related to marital compatibility, which may negatively affect family stability and lead to an escalation of marital disputes. It also showed a strong positive correlation between building trust today between spouses and the man's submission to his wife. At the end of the research, a set of recommendations were presented that aim to enhance awareness of the importance of balancing mutual interest and maintaining the status of each party in the family, in addition to emphasizing the importance of equal marital dialogue in building a stable family.
Keywords: Excessive Interest; Husband; Wife; Status; Family